The effect of short-term intermittent fasting on improved body composition and sports performance - Castillo, Gregory Alden C. 2001-
Studies on intermittent fasting (IF) have become popular in recent years due to its effects on weight loss, as well as its applications for Islamic athletes who follow Ramadan IF. Apart from its effects on weight loss, IF is also known for its benefits on metabolism and its potential adverse effects on sports performance. However, these adverse effects must still be studied since they have been inconsistent, minimal, and could result from either fatigue due to fasting states or a lack of water for Ramadan IF. Participants in the study were divided into the IF group and the control (CG) group. IF group participants recorded a decrease in body fat percentage coupled with a decrease in time to exhaustion (TTE) results. CG group participants on the other hand have shown an increase in body fat percentage with an increase in TTE results. All participants recorded sub-optimal energy availability scores, however, none of them went below the minimum threshold. These results highlight the necessity for personalized diets for athletes of a high caliber for positive effects on both body composition and sports performance. The use of IF should be used for recreational athletes who focus on fitness and physique goals. This study would then highlight that the known positive impacts on health and body composition will not negate the inconsistent adverse effects seen in previous studies and supplement knowledge on limited research on time-restricted feeding without post-tests done in diet-induced fatigue.